2011
DOI: 10.1007/s00424-011-1035-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of TM6 and TM12 to the pore of CFTR identified by three sulfonylurea-based blockers

Abstract: Previous studies suggested that four transmembrane domains 5, 6, 11, 12 make the greatest contribution to forming the pore of the CFTR chloride channel. We used excised, inside-out patches from oocytes expressing CFTR with alanine-scanning mutagenesis in amino acids in TM6 and TM12 to probe CFTR pore structure with four blockers: glibenclamide (Glyb), glipizide (Glip), tolbutamide (Tolb), and Meglitinide. Glyb and Glip blocked wildtype (WT)-CFTR in a voltage-, time-, and concentration-dependent manner. At V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 53 publications
5
37
0
Order By: Relevance
“…Compounds that block anion conduction through CFTR channels (Sheppard and Robinson, 1997;Cai et al, 1999;Muanprasat et al, 2004;Sheppard, 2004;Zhang et al, 2004a;Sonawane et al, 2006Sonawane et al, , 2007de Hostos et al, 2011;Cui et al, 2012) may lead to treatments for secretory diarrhea and polycystic kidney disease. The CFTR-blocking small molecule 3-(3,5-dibromo-4-hydroxyphenyl)-N-(4-phenoxybenzyl)-1,2,4-oxadiazole-5-carboxamide (iOWH032), which currently is being studied in a clinical trial (de Hostos et al, 2011), is structurally related to the pore blocker N-(2-naphthalenyl)- [(3,5-dibromo-2,4-dihydroxyphenyl)methylene]glycine hydrazide (GlyH-101) (mol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds that block anion conduction through CFTR channels (Sheppard and Robinson, 1997;Cai et al, 1999;Muanprasat et al, 2004;Sheppard, 2004;Zhang et al, 2004a;Sonawane et al, 2006Sonawane et al, , 2007de Hostos et al, 2011;Cui et al, 2012) may lead to treatments for secretory diarrhea and polycystic kidney disease. The CFTR-blocking small molecule 3-(3,5-dibromo-4-hydroxyphenyl)-N-(4-phenoxybenzyl)-1,2,4-oxadiazole-5-carboxamide (iOWH032), which currently is being studied in a clinical trial (de Hostos et al, 2011), is structurally related to the pore blocker N-(2-naphthalenyl)- [(3,5-dibromo-2,4-dihydroxyphenyl)methylene]glycine hydrazide (GlyH-101) (mol.…”
Section: Introductionmentioning
confidence: 99%
“…GlyH-101 carries a net negative charge (pK a ϭ 5.5) under physiological conditions (pH ϳ7.4) and is thought to block the CFTR by entering the channel from the extracellular side and binding to a site within the pore (Muanprasat et al, 2004;Sonawane et al, 2006Sonawane et al, , 2007. Although the mechanisms of action of pore blocking small molecules thought to act from the cytosolic side of the CFTR channel have been explored extensively in electrophysiological studies and amino acid substitution analyses (Sheppard and Robinson, 1997;Hwang and Sheppard, 1999;Zhou et al, 2002Zhou et al, , 2010Linsdell, 2005;Cui et al, 2012), the mechanism of action of GlyH-101 has been less well studied. We chose to investigate the binding of GlyH-101 because the open-channel blocker seemed likely to bind in a narrow part of the CFTR pore.…”
Section: Introductionmentioning
confidence: 99%
“…Based on functional data and homology models, CFTR has been predicted to contain five functional domains: two membranespanning domains (MSDs), each including six transmembrane (TM) helices; two nucleotide binding domains (NBD1 and NBD2); and a unique regulatory (R) domain, which carries multiple protein kinase A (PKA) consensus phosphorylation sites and is unique to CFTR in the ABC superfamily (1)(2)(3)(4)(5)(6). Functional studies from multiple groups have suggested that TM6 plays an essential role and TM12 contributes less to anion conduction and permeation properties in the CFTR channel pore (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…We reported previously that human wild type CFTR (WT-CFTR) exhibits a predominant full open state with two rare subconductance states (s1 and s2). Infrequent subconductance behavior is seen in some CFTR mutants, such as T338A/C-and S1141A-CFTR (7,12). However, subconductance states are dominant events with short burst durations in CFTR channels bearing known salt bridge mutations, such as R352A, R347H, D993R, and D924R (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation